The Impact of Environmental Management System on Firm Value Through Carbon Emission Disclosure and Environmental Performance - Limang, Andrian; Ng, Suwandi; Tangke, Paulus (AJAR, 2024)
The purpose of this study was to examine the impact of environmental management systems on firm value through the mechanism of carbon emission disclosure and environmental performance. This study uses secondary data. The data sources in this study are annual reports and sustainability reports of nonfinancial companies listed on the Indonesia Stock Exchange for the period 2019 until 2022. The sample selection was carried out using a purposive sampling method, with a total sample of 32 non-financial companies. This study uses path analysis and statistical tests of linear regression. The results of this study indicate that the environmental management system has a positive and significant effect on carbon emission disclosure. The environmental management system has a positive and significant effect on environmental performance. Carbon emission disclosure and environmental performance have a positive and significant effect on firm value. In addition, the results of the Sobel test show that carbon emission disclosure and environmental performance can mediate the impact of environmental management systems on firm value.